Management of Health Services through Telemonitoring in The Elderly - Risky Ika Riani; Sri Achadi Nugraheni; Farid Agushybana (Jurnal Aisyah : Jurnal Ilmu Kesehatan, 2022)
The increasing number of elderly people around the world will increase chronic diseases and multimorbidity. A consistent health care system at home that can help the elderly in dealing with their illness is needed. Effective health management can slow disease progression and minimize complications. Telemonitoring is part of a telehealth system that uses a patient management approach by combining various information technologies to monitor patients remotely via smart phones, which can be considered as a solution, because it has been proven to reduce treatment costs, shorten length of stay, reduce hospital readmission rates, and improve the quality of life of elderly patients.